Manuscript, Philology, and Indonesian Islam - Fachri Aidulsyah; Saiful Hakam (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2022)
The manuscript serves as a window into a nation's civilisation. Manuscripts, also known as